2009
DOI: 10.1590/s0100-40422009000500012
|View full text |Cite
|
Sign up to set email alerts
|

Influência da ação das enzimas alcalase e flavourzyme no grau de hidrólise das proteínas de carne de frango

Abstract: Recebido em 15/4/08; aceito em 12/1/09; publicado na web em 11/5/09 INFLUENCE OF ALCALASE AND FLAVOURZYME PERFORMANCE ON THE DEGREE OF HYDROLYSIS OF THE PROTEINS OF CHICKEN MEAT. To study the action of Alcalase and Flavourzyme on the proteins of chicken meat, the influence of the substrate concentration [S], enzyme concentration [E] and hydrolysis time on the degree of hydrolysis (DH) of the proteins was evaluated. The highest DH for breast meat was obtained with a [S] of 3.3% (w/v), with a [E] of 6% (w/w) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
0
17
0
3
Order By: Relevance
“…This difference can be partially explained by an interference of lipids in the batch experiments, which was not observed in the preliminary tests, given the lower volume of the solution. Schmidt & Salas-Mellado (2009) reported that the high amount of lipids leads to a lower degree of hydrolysis. The author also argue that a high amount of lipids could form complexes protein/lipids, which would be more resistant to enzymatic hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…This difference can be partially explained by an interference of lipids in the batch experiments, which was not observed in the preliminary tests, given the lower volume of the solution. Schmidt & Salas-Mellado (2009) reported that the high amount of lipids leads to a lower degree of hydrolysis. The author also argue that a high amount of lipids could form complexes protein/lipids, which would be more resistant to enzymatic hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…A fim de considerar a possibilidade de que uma variável é preditiva, o valor de F calculado deve ser de 3 a 5 vezes maior que o F Fisher (Schmidt & Salas-Mellado, 2009) Com relação à PA, maiores valores foram obtidos quando se utilizaram maiores concentrações da solução de sacarose (Figura 1B). O aumento da concentração da solução de sacarose gerou fluxos de massas que ocasionaram uma variação da concentração da solução e diminuição dos gradientes de concentração entre a fruta e a solução osmótica, ao longo do processo, promovendo um aumento na taxa de perda de água (Dalla & Giroux, 2001).…”
Section: Methodsunclassified
“…The real values for the levels of each independent variable (X i ) were represented by the factors, defined from literature searches regarding meat raw materials (Schmidt & Salas-Mellado, 2009), and similar industrial processes from BRF-Foods.…”
Section: Central Composite Rotatable Design For Enzymatic Hydrolysimentioning
confidence: 99%
“…Among the enzymes of microbial origin, the most widely used in the production of protein hydrolysates, either commercially or for research studies, is Alcalase 2.4L™, a bacterial endopeptidase developed by the company Novozymes, originated in the submerged fermentation process with the microorganism Bacillus licheniformis (Alavi, Jamshidian, & Rezaei, 2019;Bernardi et al, 2016;Corîci et al, 2011). This enzyme is classified as a subtilisin, a serine protease that is known to operate under moderate conditions of alkalinity (6-10) (Roslan et al, 2014) compared to the neutral or acidic enzymes, and temperatures of 35-70 C (Schmidt & Salas-Mellado, 2009) with optimum temperature of 55 C (Bhaskar, Benila, Radha, & Lalitha, 2008;See, Hoo, & Babji, 2011) and 60 C (Amiza, Nurul Ashikin, & Faazaz, 2011;Normah, Jamilah, Saari, & Yaakob, 2005), acting in the peptide bonds contained in the hydrophobic residues. The prominence of Alcalase 2.4L™ is found to be one of the highly efficient enzymes for the protein hydrolysis due to its ability to catalyze protein hydrolysis reaction with high degree of hydrolysis (DH) in a relatively short period (Adler-Nissen, 1986;Aspmo, Horn, & Eijsink, 2005).…”
mentioning
confidence: 99%